Assessment of measurement uncertainty in optical marker tracking of high-speed motion - Lückemann, P.; Forrester, S.; Mears, A.; Shepherd, J.; Roberts, J. (Proceedings, 2020)
Optical marker tracking is used in research environments to understand the dynamics of moving objects of interest. Due to the complexity of the systems and the wide field of applications, there is no simple method to assess system accuracy. In this approach, a driver clubhead functioned as a rigid body and was tracked during the delivery phase of the golf swing. Marker tracking uncertainty was assessed by measures of inter-marker distance errors. The effect of swing speed on marker tracking uncertainty was tested in the range 0 m/s (static) to 50 m/s. Results demonstrated that the rigid body position in the capture volume has a large effect on marker tracking uncertainty. Positive correlations were found between marker tracking uncertainty and swing speed. Marker size and number of cameras used for marker reconstruction were optimised to provide mean marker tracking uncertainties around the tee position of below 0.13 mm.